Multiscale Characterization of Composite Electrode Microstructures for High Density Lithium-ion Batteries Guided by the Specificities of Their Electronic and Ionic Transport Mechanisms. Issue 10 (10th June 2020) - Cadiou, F.; Douillard, T.; Besnard, N.; Lestriez, B.; Maire, E.
Abstract : The microstructures of Li-ion positive composite electrodes designed for EVs have been characterised at different scales and in particular by FIB/SEM nanotomography. These electrodes are composed of Li(Ni0.5 Mn0.3 Co0.2 )O2, carbon black (CB), and polyvinylidene fluoride (PVdF). The component proportions in the electrodes and the electrode densities were varied. Specific image analysis tools have been developed to quantify the microstructure parameters that will influence the transport and exchange properties of ionic and electronic charges during battery operation. Different porosities have been highlighted, in particular the micrometric porosity which appears to be the most effective for the ion diffusion in the liquid electrolyte due to its low tortuosity and large intra-connectiviy. Different parallel paths for the transport of electrons in solid phases such as the CB/PVdF percolating network and a hybrid one consisting of CB/PVdF islands distributed on the NMC cluster surface and the NMC grains pertaining to these clusters. This last network can be effective when the CB/PVdF islands allow the electrons to short-circuit the resistive NMC grain boundaries.